Aiming for “brand bonuses” in times of budget cuts - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2009)
Branding, perceived by the bean-counters as an expense item, is always among the first to go during recessions. In its place are price cuts and price promotions aimed at delivering value to customers. The common (and predictable) belief is to stimulate demand quickly, so as to sustain production and operations during the trying times. After all, brand equity cannot possibly help close a sale or bring in the cash –- or can it? To answer this question, SMU’s Provost, Rajendra K. Srivastava, examined the financial performance of brands during a downturn in a hunt for the elusive “brand bonus”.